Carbon Dioxide (CO2) emissions and ecological effects of biomass composts - Bulfa Jr., Arsenio D.; C. Cubelo, Jose Edwin (Asia-Pacific Journal of Science and Technology, 2025)
Composts from biomass wastes are a source of plant nutrients and help improve soil quality. An experiment laid out in a split-plot in a completely randomized design was conducted to determine the chemical properties of composts produced from the decomposition of biomass wastes mixtures such as poultry manure + rice straw (PMRS) and poultry manure + carbonized rice hull (PMCRH) with different C:N ratios and their application effects on corn growth, soil chemical properties, earthworm behavior, and CO2 emissions. Results show that the chemical properties of composts were relatively high; however, increasing the C:N ratio led to reductions in pH, organic carbon (OC), total P, total K, and total NPK. Compost application significantly enhanced corn growth and improved soil chemical properties. Root weight, root length and plant height were significantly increased in both PMRS and PMCRH-treated soils. No significant avoidance behavior was observed among earthworms in compost-treated soils indicating suitability for soil fauna. In the incubation setup, a significant amount of CO2 was captured in the soil treated with PMCRH. The application of both compost types is recommended as it improved soil health, enhanced plant growth, and was safe for soil organisms. PMCRH compost application is a potential carbon capture and storage strategy that may help reduce CO2 emissions. This approach supports a sustainable food production system with net carbon sequestration and provides an optimal, localized, and environmentally sustainable biomass waste management solution.